Software Development Sistem Informasi Kursus Mengemudi (Kasus: Kursus Mengemudi Widi Mandiri) - Nugroho, Nurhasan; Rahmanto, Yuri; Rusliyawati, R; Alita, Debby; Handika, H (STIKOM Tunas Bangsa Pematangsiantar, 2021)
Widi Mandiri is an institution that provides training courses for driving four-wheeled vehicles. In managing data, Widi Mandiri uses records in certain forms or books from participant registration, scheduling and all business processes. With the existing system, there are several obstacles that hinder the conduct of business at Widi Mandiri. For that we need a driving course information system that helps in the management of all business activities at Widi Mandiri. The system development is carried out by using the extreme programming (XP) system development approach. The research has produced a system that can manage driving course data from registration of course participants, booking courses and cars to scheduling according to the schedule of course participants and instructors. Based on usability testing, the average value was 85.8%, and was in the good category